PENGARUH MEDIA PEMBELAJARAN GEOGEBRA PADA MATERI BANGUN RUANG TERHADAP KEMAMPUAN SPASIAL SISWA KELAS VI SD - jalizar, Nurrahmi Gussarsi; Yullys Helsa; Masniladevi; Fadila Suciana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of GeoGebra as a learning media on students' spatial ability in learning solid geometry at the elementary school level. This research employed a quantitative approach using an experimental method with a posttest-only control design. The participants were divided into two groups: an experimental group taught using GeoGebra and a control group taught using conventional methods. The instrument used was an essay test that had been validated and tested for reliability. The results showed that the average posttest score of the experimental group (77.38) was higher than that of the control group (60.38). Hypothesis testing using a t-test indicated a significance value of 0.000 (<0.05), which means that GeoGebra has a significant effect on students' spatial ability. Therefore, GeoGebra can be considered an effective learning media to improve spatial ability in learning solid geometry.